Public Budgetary Decision-making between rationality Approaches and incrementalism - MESSAI, Mohamed (Journal of Excellence for Economics and Management Research, 2026)
The decision-making marks a crucial stage in public budgeting process. The success of the ultimate decision depends on how It is made, especially how the information in possession of the decision-maker is used. To provide answers about that, this research paper addresses the most important approaches to budgetary decision-making, that are rational approaches on the one hand, and incrementalist approach on the other hand. The study concluded that contrary to what the pure rationality approach proposes, that is analysis of all available information, determination of all possible alternatives to select the best of them, the bounded rationality approach demonstrates that this is not possible because of the limits of human capacities that often make the decision-maker content with satisfying alternative, without seeking the optimal alternative. The multiple rationality approach adds to this the need to use both intuitive and analytical cognition for decision-making. For its part, the incrementalist approach argues that decision making is not some conscious form of pure rationality, but is a process of incrementally adjusting existing practices to establish or reestablish consensus reached through a political, power-oriented bargaining, with emphasis on the proposition that budgetary decisions are necessarily political